Heidegger and music - Rentmeester, Casey; Warren, Jeff R. 1977- (Rowman & Littlefield, 2022)
"This volume, the first to tackle Heidegger and music, features contributions from philosophers, musicians, educators, and musicologists from many countries throughout the world, utilizes Heidegger's philosophy to shed light on the place of music in different contexts and fields of practice"--
Keywords: Heidegger, Martin -- 1889-1976; Musikphilosophie; Music / Philosophy and aesthetics; Music and philosophy; Heidegger, Martin / 1889-1976